Pengaruh Pembelajaran Al-Qur'an terhadap Karakter Sosial Siswa SD Islam Ibnu Umar Tangerang Selatan - Yudistira, Satria; Nuryaman, Muhammad; Lumaela, Ibni Fikri (Lembaga Yasin AlSys, 2025)
Learning the Qur'an has an important role in shaping students' social character and behavior. This is because the Qur'an is a source of guidance for life so that when someone understands it will be much better when applied. This study aims to analyze the influence of Qur'anic learning on students' social character at SD Islam Ibnu Umar Tangerang Selatan. The research employs a quantitative method with multiple linear regression analysis. The sample consists of 100 students from grades 4, 5, and 6, selected using purposive sampling techniques. The results indicate that Qur'anic learning significantly influences students' social character, with a significance value (p-value) of 0.042 (p < 0.05). These findings suggest that the better the Qur'anic learning implementation, the more positive students' social character development becomes. Therefore, schools should continue to enhance Qur'anic learning programs as part of character education to foster a morally upright generation.